ADSORPSI ION EMAS(III) DALAM SISTEM MULTILOGAM Au/Ni/Ag - Julita Manuhutu; Nuryono Nuryono; Sri Juari Santosa (Molluca Journal of Chemistry Education (MJoCE), 2011)
Sorption of gold(III) ion in multi-metal system Au/Ni/Ag on amino silica hybrid (ASH) column has been studied. ASH was synthesized by sol gel process with sodium silicate (Na2SiO3) from rice husk ash (RHA) as precursor. ASH was synthesized by adding 3M of hydrochloride acid solution to the mixture of (3-aminopropyl)trimethoxysilane and Na2SiO3 solution until pH 7 (neutral). ASH was characterized by infrared (IR) spectroscopy and X-ray diffraction (XRD). Adsorption of multi-metal (Au/Ni/Ag) system was carried out with a column technique. The adsorbed metal ions [Au(III), Ni(II), and Ag(I)] were quantitavely calculated based on the difference of metal ion concentration before and after adsorption analyzed using atomic absorption spectroscopy (AAS). Desorption of Au(III), Ni(II), and Ag(I) from ASH was conducted by using thioruea in hydrochloride solution with variation of concentration. Desorbed metal ions were determined using AAS. The FTIR characterization indicated that ASH was successfully synthesized, as shown with the presence of spesific absorption of functional groups such as silanol (Si-OH), siloxane (Si-O-Si), amino (-NH2), dan methylene (-CH2-). The XRD data showed that the structure of ASH was amorphous. Study of adsorption Au(III) on HSA column indicated that the Au(III) was adsorbed more than the other two metal ions